Northern Hemisphere Glaciation, African climate and human evolution. (15th September 2021) - Trauth, Martin H.; Asrat, Asfawossen; Berner, Nadine; Bibi, Faysal; Foerster, Verena; Grove, Matt; Kaboth-Bahr, Stefanie; Maslin, Mark A.; Mudelsee, Manfred; Schäbitz, Frank
Abstract: The hypothesis of a connection between the onset (or intensification) of Northern Hemisphere Glaciation, the stepwise increase in African aridity (and climate variability), and an important mammalian (including hominin) species turnover is a textbook example of the initiation of a scientific idea and its propagation in science. It is, however, also an example of the persistent popularity of a hypothesis despite mounting evidence against it. A critical review of key publications on the topic and statistical re-analysis of key records of global ice volume and African climate leads to three conclusions: (1) The Northern Hemisphere Glaciation was a gradual process occurring between ∼3.5 and 2.5 Ma, not a single event at ∼2.8 Ma or at any other time. (2) A consistent stepwise (+/−0.2 Ma) transition toward greater aridity in Africa at ∼2.8 Ma does not exist; instead, there are regionally different, gradual transitions partly in connection with the intensification of the Northern Hemisphere Glaciation, but above all with the establishment of the tropical Walker Circulation after ∼2 Ma. (3) Mammalian (including hominin) species turnovers at this time also appear to have been gradual, rather than stepwise. Highlights: We falsified the hypothesis of a connection between Northern Hemisphere Glaciation, African climate and human evolution.